Fatty acid profiles of three commercial shrimp from southeastern Brazil - Gonçalves, Geslaine Rafaela Lemos [UNESP]; Denadai, Ana Clara [UNESP]; Sousa, Aline Nonato [UNESP]; Castilho, Antonio Leão [UNESP]; De Troch, Marleen (My University, 2021)
This study describes the fatty acid (FA) composition of three commercially important species of shrimp, from a region with the largest mangrove forests in Brazil. Fatty acids composition shows the nutritional quality of the shrimps and their importance as a node of energy transfer in the trophic web. The FA profiles of three shrimp species with different life cycles were collected from Cananéia, São Paulo, Brazil: Xiphopenaeus spp. (offshore), Penaeus schmitti and Penaeus paulensis (both mangrove dependent). A total of 29 different FAs were detected in their FA profile. However, each species presented a different profile of FAs. The fatty acids 16:0, 18:0, 18:1ω9, 20:5ω3 (EPA) and 22:6ω3 (DHA) contributed for the significant differences between the shrimp species. The restricted occurrence of Xiphopenaeus spp. in the marine region explained the difference in the FA concentration compared with the P. schmitti and P. paulensis shrimps, that spend part of their life cycle in the mangrove. The study highlights that these shrimps are essential sources of FAs in the trophic web and are valuable for human health, especially the polyunsaturated FAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA).
Keywords: Benthic consumers; Fatty acids; Mangrove; P. paulensis; P. schmitti; Xiphopenaeus spp.